UJI SETTING TIME PADA MODIFIKASI ALGINAT DENGAN PENAMBAHAN TEPUNG JAGUNG (Zea mays) SEBAGAI ALTERNATIF BAHAN CETAK - Diana Setya Ningsih; Iin Sundari; Syarifah Masyithah Rizka (Journal of Syiah Kuala Dentistry Society, 2016)
Alginate is one of the impression materials that is often used in Indonesian dentistry.However in some cloistered places alginate is difficult to beobtained because of distance and limited supply. Handling this situation, modification of impression material is done by adding natural ingredient that contains polysacarida such as corn flour (Zea mays). This research aims know the knowledge about corn flour (Zea mays) addition in alginate impression material as alternative impression materialreviewed fromsetting time. Twenty four specimens in this research are divided into six groups (alginate : corn flour) they areA (100%: 0%), B (55%: 45%), C (52.5%: 47.5%), D (50%: 50%), E (47.5%: 52.5 %), and F (45%: 55%). Measurement test of setting time employs an indicator of setting time cylinder bar and made of poly (methyl methacrylate). Data is statistic analyzed using ANOVA test and posh hoc tukey. Based on ANOVA statistic test shows that the presence of corn flourdifference setting time in corn flour mixed by alginate impression material among every group. However continued test result there is no significant difference among D with C and E. the conclusion of this research is corn flour (Zea mays) can be used as alternative impression material reviewed from setting time. Getting higher the corn percentage so getting long the setting time. The consistency that approaches alginate setting time is B (55% : 45%).Keywords : Alginate, Corn Flour, Setting Time